Relationship between Academic Stress, Family and Peer Attachment with Internet Addiction in Adolescents - Putri Ariani; Suryani Suryani; Taty Hernawaty (Jurnal Keperawatan Padjadjaran, 2018)
Biological, psychological and social changes make adolescents at risk of various health problems in the community. The ease of internet access nowadays makes adolescent more vulnerable to internet addiction. In Indonesia, many studies examine the relationship between internal factors such as low self-esteem, loneliness and the type of personality with internet addiction. Further research is still needed that focuses on external factors such as academic stress, family and peer attachment. This study aimed to examine the relationship of academic stress, family and peer attachment with internet addiction in high school adolescents in Andir District, Bandung City. The study used a quantitative correlational design with a cross-sectional approach. The population was high school adolescents. A total sample of 367 adolescents was determined using the slovin formula with alpha Cronbach 0.05. Respondents were recruited using random cluster sampling. Data were analyzed using Rank Spearman and Logistic Regression. Statistical tests of academic stress variables showed, family and peer attachments were significantly related with internet addiction in adolescents (p = 0.000); family attachment variable was significantly related to internet addiction in adolescents (p = 0.000), and peer attachment was significantly related with internet addiction in adolescents (p = 0.000). Logistic regression tests showed the family attachment variable had a significant influence on internet addiction in high school adolescents. In conclusion, there are correlations between academic stress, family and peer attachment to internet addiction. The family attachment has the most significant influence with internet addiction in high school adolescents. It is essential for community mental health nurses to conduct health education to families related to the result of this study